The formation of future doctors‘ professional dialogue - Orel-Khaliq, Yu.; Орел-Халік, Юлія Владиславівна (My University, 2019)
The article is dedicated to the question of „ dialog”, „culture of dialog” „culture of professional dialog” and to analyses of ways of professional culture formation of medical students. The formation of culture of professional dialogue involves not only language education, which is aimed at the development of student's speaking competence but also at the development of general and professional culture. Future doctors should learn to find in each case a form of communication that should be suitable for the definite patient. Doctors talk with their patients in the form of a dialogue in which they discuss complaints, fillings, mental conditions, treatment and outcome of the disease, the diagnosis. In the process of communication doctors should transfer all necessary information to their patients and help them understand the peculiarities of diagnosis and medical ways of rehabilitation. During the conversation both the physician and the patient must work out a single point of view about treatment. Culture of professional dialogue is a business card of the future specialist. The manner the doctor communicates shows the level of general and professional culture of the specialist.
Keywords: dialogue; the culture of dialogue; culture of professional dialogue; formation